The Relationship Between Mothers’ Knowledge and Attitudes Toward Measles–Rubella (MR) Immunization in Children Aged 24 Months - Sri Maryani; Kismi Asih Adethia; Eka Falentina Tarigan; Ovita Sari Cantika (Knowledge Dynamics, 2025)
Introduction: Measles and rubella are infectious diseases that can affect anyone. According to the World Health Organization, in 2017 an estimated 110,000 children under five years of age died globally due to measles. This study aimed to analyze the relationship between mothers’ knowledge and attitudes toward the administration of Measles–Rubella (MR) immunization in children aged 24 months. Methods: This study employed an observational analytic design. The research was conducted at Sidomulyo Primary Health Center, Tungkal Ilir District, in May 2023. The study sample consisted of a portion of children aged two years and above, with a total sample size of 161 respondents. The sampling technique used was simple random sampling. Results: The results showed that, based on knowledge, the majority of respondents had good knowledge, accounting for 104 respondents (64.6%). Based on attitude, most respondents demonstrated a positive attitude, totaling 99 respondents (61.5%). Bivariate analysis indicated that the majority of respondents with good knowledge also had a positive attitude toward MR immunization, with 80 respondents (49.7%). The chi-square test results showed a p-value of 0.000 (p < 0.05). Conclusion: The study concluded that there is a significant relationship between mothers’ knowledge and attitudes toward the administration of Measles–Rubella (MR) immunization in children aged 24 months. It is recommended that the head of the primary health center pay attention to children who have not received MR immunization and implement outreach approaches to ensure that all children receive MR immunization.